HOW TO DO A GOOD RESEARCH - Dr. Pratap Kumar Ghori; Satabdi Mondal (International Engineering Journal For Research & Development, 2022)
In order to study about how to do a good research, at first we have to know what is research as well as a good research , Research is an in depth enquiry & scientific analysis of any social facts &phenomena , A fundamental objective of research is the social welfare as well as development of society. No good research can be done by only sake of research, each and every research should have strong necessity & importance for the root out the proper cases of any social problems & also should give an accurate remedial measures to solve the problems. But in the contemporary time unfortunately most of the academic research are doing for the sake of research in one side, and is another side research topic is choiced by the Research guide, where researcher has no freedom to choose the problems of his/her own interest, so in the beginning as well as in first step research become abuse , This type of research abuse is happening by the ignoracy of research guide, most of the research guide never give any importance on the interest or choice of researcher. that’s why most of the research has lost its objectivity and also good research are not happening. So to do a good research, every research have to follow each step very sincerely & also to follow research ethics properly.